2016
DOI: 10.2337/db16-0655
|View full text |Cite
|
Sign up to set email alerts
|

Partial Disruption of Lipolysis Increases Postexercise Insulin Sensitivity in Skeletal Muscle Despite Accumulation of DAG

Abstract: Type 2 diabetes and skeletal muscle insulin resistance have been linked to accumulation of the intramyocellular lipid-intermediate diacylglycerol (DAG). However, recent animal and human studies have questioned such an association. Given that DAG appears in different stereoisomers and has different reactivity in vitro, we investigated whether the described function of DAGs as mediators of lipid-induced insulin resistance was dependent on the different DAG isomers. We measured insulin-stimulated glucose uptake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…DAG content was measured on freeze dried liver tissue by thin layer chromatography. Lipids were extracted in chloroform-methanol (2:1) and dissolved in chloroform, before being separated (Serup et al, 2016). Lipid staining were developed by a 10% copper sulfate pentahydrate and 8% phosphoric acid solution at 120 C for 15 min, and visualized and analyzed on a Kodak image station (Kodak 2000MM, DK).…”
Section: Star+methodsmentioning
confidence: 99%
“…DAG content was measured on freeze dried liver tissue by thin layer chromatography. Lipids were extracted in chloroform-methanol (2:1) and dissolved in chloroform, before being separated (Serup et al, 2016). Lipid staining were developed by a 10% copper sulfate pentahydrate and 8% phosphoric acid solution at 120 C for 15 min, and visualized and analyzed on a Kodak image station (Kodak 2000MM, DK).…”
Section: Star+methodsmentioning
confidence: 99%
“…After a treadmill exercise, knock-out mice showed increased insulinstimulated glucose uptake along with higher (rather than lower) total DAG levels compared with wild-type mice. DAG subtype analysis revealed that 1,3-DAG increased after exercise whereas 1,2-DAG decreased after exercise (Serup et al, 2016).…”
Section: Diacylglycerolsmentioning
confidence: 95%
“…Nevertheless, multiple early studies found that PKC activation is stereospecific and achieved only by sn-1,2 DAGs (Rando & Young 1984, Boni & Rando 1985, Leach et al 1991, Wakelam 1998, Takai et al 2012. The sn-1,3 DAGs found in lipid droplets have no effect on PKC, and indeed their accumulation in muscle has recently been shown in mice to have no negative effects on insulin signalling or glucose uptake (Serup et al 2016, Lundsgaard et al 2017. Likewise, differentiation in human muscle insulin sensitivity has been found to be unrelated to sn-1,3 or sn-2,3 DAGs (Perreault et al 2018).…”
Section: Subspecies and Isoform/isomermentioning
confidence: 99%
“…Genetic mitochondrial dysfunction in mice also presents contradictory evidence: long-chain acyl-CoA dehydrogenase deficiency leads to hepatic IR (Zhang et al 2007); while defective mitochondrial substrate metabolism induced by deletion of mitochondrial transcription factor A (TFAM), apoptosis inducing factor (AIF), very long-chain acyl-CoA dehydrogenase (VLCAD) or carnitine palmitoyltransferase 2 (CPT2) protects from diet-induced obesity and IR (Wredenberg et al 2006, Pospisilik et al 2007. These discrepancies may well reflect homeostatic compensatory mechanisms responding to either elevated lipid availability or dysfunctional mitochondria (Turner et al 2007, Serup et al 2016. Apparent regulatory redundancies suggest the biological relevance of mitochondrial FAO, regardless of whether its deterioration is a consequence or stimulus of lipid accumulation.…”
Section: Insulin Resistance and Lipid Metabolismmentioning
confidence: 99%